USE OF THE OPENLABYRINTH SOFTWARE FOR AUTHORING VIRTUAL PATIENTS IN DENTAL MEDICINE I - Raphaël Mille; Oana Ţănculescu; Monica Andronache; Gabriela Ifteni; Alina Apostu; Nicoleta Ioanid; Dragoş Virvescu; Adrian Doloca (Romanian Society of Oral Rehabilitation, 2019)
The development and use of virtual patient software interests more and more universities that come together and work together, thanks to the Internet to exploit the best tools and share their progress. Among the existant virtual patient software OpenLabyrinth was selected for authoring patients. First the possibilities offered by the software are presented, then two virtual patients were authored for exemplification, and described with their limits and challanges in the two parts of the present article.